Mitigation of Cryopreservation Induced Changes in Murrah Buffalo (Bubalus bubalis) spermatozoa using L-Cysteine Hydrochloride - Alam, Kabir; Srivastava, Sushant; Jaiswal, Ankit; Kumar, Rajesh; Verma, Abhishek Kumar (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
This investigation was carried out with the objective of finding improvements in the quality of frozen semen from buffalo bulls with the incorporation of cysteine as an additive in tris dilutor. Thirty-six ejaculates from six Murrah buffalo bulls of 6-8 years of age group were collected in sterilized artificial vagina to evaluate the effect of additives at the post-dilution and post-thaw stages. The semen sample was extended with Tris-Citric-acid-Fructose-Egg-Yolk–Glycerol (TFYG) extender and was divided into two groups: Group I without any additive served as control (C) group, while Group II, extender supplemented with L-cysteine hydrochloride (1.0 mM) served as treatment (T) group. Progressive sperm motility, live spermatozoa, sperm abnormalities, and enzyme leakage (AST and ALT) were evaluated at both post-dilution and post-thaw stages. There was significant (p<0.01) improvement in progressive motility and live spermatozoa, as well as a significant (p<0.01) decrease in sperm abnormalities and enzyme leakage (AST and ALT) in the cysteine-treated group compared to the control group. The per cent sperm abnormalities had significant negative correlations with sperm motility and viability, and positive correlations with seminal AST and ALT activity at both on dilution and post-thaw stage of semen. It was concluded that the addition of 1.0 mM L-cysteine hydrochloride to the Tris extender significantly (p<0.01) improves the quality of cryopreserved bubaline semen.